2013
DOI: 10.1155/2013/582079
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Biological Activity of 4-(2-Hydroxy-5-(aryl-diazenyl)phenyl)-6-(aryl)pyrimidin-2-ols Derivatives

Abstract: With the aim of synthesizing new heterocyclic compounds and exploring biological potency, new series of chalcones, that is, 3-(2-hydroxy-5-(aryl-diazenyl)phenyl)-1-(aryl)prop-2-en-1-one and their pyrimidine derivatives, that is, 4-(2-hydroxy-5-(aryl-diazenyl)phenyl)-6-(aryl)pyrimidin-2-ols were synthesized using different aromatic amines and salicylaldehyde as starting moieties. The structures of newly synthesized compounds were confirmed using different spectroscopic techniques such as IR, 1H-NMR, 13C-NMR, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In addition, the overlapping CH signals appeared at 7.16 -8.35 ppm ascribing to the aromatic protons of the two phenyl rings. The noted chemical shift of H 8 , H 9 , H 22 (δ = 7.99, 8.18 ppm) is a characteristic downfield value of protons in o-position for the diazinyl moiety, whereas the downfield shift of the singlet peak of H 24 (8.07) and the up-filed shift of H 20 (7.16) suggested the presence of the hydroxyl group at ortho and meta positions to these two protons respectively [52][53][54]. The proton of the triazole ring appears at 8.35 ppm and a characteristic exchangeable proton of OH appears at 10.32.…”
Section: Nuclear Magnetic Resonance (Nmr)mentioning
confidence: 99%
“…In addition, the overlapping CH signals appeared at 7.16 -8.35 ppm ascribing to the aromatic protons of the two phenyl rings. The noted chemical shift of H 8 , H 9 , H 22 (δ = 7.99, 8.18 ppm) is a characteristic downfield value of protons in o-position for the diazinyl moiety, whereas the downfield shift of the singlet peak of H 24 (8.07) and the up-filed shift of H 20 (7.16) suggested the presence of the hydroxyl group at ortho and meta positions to these two protons respectively [52][53][54]. The proton of the triazole ring appears at 8.35 ppm and a characteristic exchangeable proton of OH appears at 10.32.…”
Section: Nuclear Magnetic Resonance (Nmr)mentioning
confidence: 99%
“…Dextrose agar was used to determine antifungal properties against Candida albicans and Aspergillus niger. All the compounds showed considerable antimicrobial activity but it was concluded that pyrimidine derivatives having nitro group in their structure showed better antimicrobial properties as compared to other chalcones derivatives [33]. [2,3d] ]pyrimidin-10(4H)one exhibited maximum antimicrobial activity [34].…”
Section: Antimicrobial Properties Of Functionally Substituted Chemicamentioning
confidence: 99%
“…[34,35] The general route for the synthesis chalcones involve Claisen-Schmidt condensation between acetophenone derivatives and aromatic aldehydes, utilizing strong acidic or basic reagents/catalysts like NaOH, KOH, AlCl 3 and HCl. [36] These methods however have drawbacks associated with catalyst recovery, side-product formation, less product selectivity, longer reaction time, harsh reaction conditions and complicated isolation of products. [37] Eventually, a number of environmentally benign strategies were developed with ionic liquids, [25,[38][39][40] glycerine, [41] microwave [42] and ultrasound-assisted conditions [43] for the efficient synthesis of chalcones.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, chalcones represent a class of α, β‐unsaturated aromatic ketones that are present as the core unit in an array of biologically active molecules with antibacterial, anti‐inflammatory, antiviral, anticancer and antifungal activities [34,35] . The general route for the synthesis chalcones involve Claisen‐Schmidt condensation between acetophenone derivatives and aromatic aldehydes, utilizing strong acidic or basic reagents/catalysts like NaOH, KOH, AlCl 3 and HCl [36] . These methods however have drawbacks associated with catalyst recovery, side‐product formation, less product selectivity, longer reaction time, harsh reaction conditions and complicated isolation of products [37] .…”
Section: Introductionmentioning
confidence: 99%